STRAINS IN TRADITIONAL FAMILY VALUES IN A YORUBA COMMUNITY: A STUDY OF FAMILIES IN AKOKO-LAND IN ONDO STATE, NIGERIA - Olayiwola O., Fasoranti; Owagbemi, Olusola Gabriel (European Scientific Journal, ESJ, 2012)
The study examines the changes in Yoruba traditional family values, using Akoko communities as case study. Modernization theory was employed to explain how western culture has been diffused into the developing countries, now changing the Yoruba family values. Two hundred and fifty copies (250) of the questionnaire schedule which addresses bio-social variables, respondents’ attitudinal change towards extended family relationships (affairs) were administered to randomly sampled households drawn from five (5) clusters within the Akoko South West LGA of Ondo state. The result shows that the emphasis on extended tie has drastically reduced. There is a popular clamour for women empowerment, and this has led to a dual-occupational system between couples. Also, there is a pervasive flair for either church/mosque or court/statuary marriages even after traditional ‘idana’ rite. The paper suggests that proper selection of mates through counselling and cultural practise(s) promises to drastically reduce the high rate of divorce in modern times. Finally, the issue of dual-occupation should be well managed, so as not to be at the detriment of the child(ren)’s up-bringing.